Validating a framework of stakeholders in connection to business sustainability efforts in supply chains. Issue 1 (6th February 2017) - Ferro, Carlos; Padin, Carmen; Svensson, Göran; Sosa Varela, Juan Carlos; Wagner, Beverly; Høgevold, Nils M.
Abstract : Purpose: The purpose of this study is two-fold: to determine the extent to which companies' efforts aimed at sustainable business practices consider stakeholders in their organisations and business networks, the marketplace and society; and to validate or refute a stakeholder framework of business sustainability efforts within focal companies, the marketplace, society and business networks. Design/methodology/approach: The study is based on a questionnaire survey targeting large companies across industries and sectors in Spain. The sample consisted of 231 companies generating a useable response rate of 38.5 per cent. Exploratory factor analysis was performed on a cross-industry sample to test a five-dimensional framework. Findings: This study reports on the validation of initial and refined factor solutions. The factor analysis confirmed five stakeholder dimensions related to business sustainability efforts of organisations, their business networks, marketplace and society. The validated results indicate satisfactory convergent, discriminant and nomological validity and reliability through time and across contexts. Research limitations/implications: The stakeholder framework in connection with business sustainability efforts in supply chains consisting of five factors was validated: the focal company, downstream stakeholders, societal stakeholders, market stakeholders and upstream stakeholders. Suggestion for further research is provided. Practical implications: The validated framework of stakeholders allows an insight into the environment in which stakeholders operate and how they influence the focal company. Originality/value: The manuscript contributes to the validation of a stakeholder framework of business sustainability efforts within focal companies, their business networks, the marketplace and society. The measurement properties provide support for acceptable validity and reliability across contexts and through time.